N-Fused quinoxalines and benzoquinoxalines as attractive emitters for organic light emitting diodes - Lindner, Benjamin; Zhang, Yexiang; Höfle, Stefan; Berger, Nancy; Teusch, Claudia; Jesper, Malte; Hardcastle, Kenneth I.; Qian, Xuhong; Lemmer, Uli; Colsmann, Alexander; Bunz, Uwe H. F.; Hamburger, Manuel (Journal of materials chemistry. C, Materials for optical and electronic devices, 2013)
We describe the modular synthesis of quinoxaline fluorophores exhibiting strong fluorescence over the whole visible spectrum. Based on their fluorescence quantum yield, frontier orbital energies and solid-state aggregation behavior, several compounds work well in fluorescent organic light emitting diodes (OLEDs) with luminances over 1000 cd m−2 at 8 V driving voltage.